2011
DOI: 10.1118/1.3533720
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric uncertainty analysis for photon‐emitting brachytherapy sources: Report of AAPM Task Group No. 138 and GEC‐ESTRO

Abstract: This report addresses uncertainties pertaining to brachytherapy single-source dosimetry preceding clinical use. The International Organization for Standardization ͑ISO͒ Guide to the Expression of Uncertainty in Measurement ͑GUM͒ and the National Institute of Standards and Technology ͑NIST͒ Technical Note 1297 are taken as reference standards for uncertainty formalism. Uncertainties in using detectors to measure or utilizing Monte Carlo methods to estimate brachytherapy dose distributions are provided with disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(150 citation statements)
references
References 95 publications
5
143
1
1
Order By: Relevance
“…These uncertainties are employed to calculate a cumulative uncertainty (CU) for each patient before and after X‐ray imaging (XC) of the patient setup using the model developed in this work and the GUM report and AAPM TG‐138 20 , 21 , 22 . The CU before XC represents an evaluation for all combined uncertainties induced by the different components of the SRS/SRT Brainlab system for the different patients, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These uncertainties are employed to calculate a cumulative uncertainty (CU) for each patient before and after X‐ray imaging (XC) of the patient setup using the model developed in this work and the GUM report and AAPM TG‐138 20 , 21 , 22 . The CU before XC represents an evaluation for all combined uncertainties induced by the different components of the SRS/SRT Brainlab system for the different patients, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CU after XC which remains in treatment of most SRS/SRT patients is 3.29 mm and 1.43 mm for this model and GUM, respectively. The GUM expanded uncertainty after XC is 2.86 mm which is obtained by multiplying the GUM cumulative accuracy with a factor of 2 20 , 21 , 22 . CU after XC is the same uncertainty for all patients because it results from systematic uncertainties that are associated with software and hardware components of the SRS/SRT Brainlab system that are not related to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in literature, 14 , 15 the HDR VCBT has some significant uncertainties. The uncertainties which existed in this study include source strength (2%); treatment planning (3%); medium dosimetry corrections (1%); volume contouring (3%); and dose delivery, including registration of applicator geometry to anatomy (5%), and interfraction/intrafraction changes between imaging and dose delivery (5%).…”
Section: Discussionmentioning
confidence: 94%
“…The dose rate constants varied with different coating thicknesses, coating mass densities, photon interaction cross‐section libraries, and photon emission spectrum types 16, 26. Aryal P et al30 found that varying 125 I coating thickness, coating mass density, photon cross‐section library, and photon emission spectrum for the model IA125I A 125 I seed changed the dose rate constant by up to 0.9%, about 1%, about 3%, and 3%, respectively, in comparison to the proposed standard value of 0.922 cGy·h1·U1.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainties associated with our TLD measurements were estimated by following the guidelines of the AAPM TG‐138 and TG‐43U1 reports 16, 26. The uncertainty associated with TLD‐seed relative positioning should take into account the 0.05 mm machining tolerance of the PMMA phantom reported by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%